Differences in the periodontal microbiome of successfully treated and persistent aggressive periodontitis. (26th June 2020) - Nibali, Luigi; Sousa, Vanessa; Davrandi, Mehmet; Spratt, David; Alyahya, Qumasha; Dopico, Jose; Donos, Nikos
Abstract: Aims: The primary aim of this investigation was to analyse the periodontal microbiome in patients with aggressive periodontitis (AgP) following treatment. Methods: Sixty‐six AgP patients were recalled on average 7 years after completion of active periodontal treatment and had subgingival plaque samples collected and processed for 16S rRNA gene sequencing analyses. Results: Of 66 participants, 52 showed persistent periodontal disease, while 13 participants were considered as "successfully treated AgP" (no probing pocket depths >4 mm) and 1 was fully edentulous. Genera associated with persistent generalized disease included Actinomyces, Alloprevotella, Capnocytophaga, Filifactor, Fretibacterium, Fusobacterium, Leptotrichia, Mogibacterium, Saccharibacteria [G‐1], Selenomonas and Treponema . "Successfully treated" patients harboured higher proportions of Haemophilus, Rothia, and Lautropia and of Corynebacterium, Streptococcus and Peptidiphaga genera. Overall, patients with persistent generalized AgP (GAgP) revealed higher alpha diversity compared to persistent localized AgP (LAgP) and stable patients ( p < .001). Beta diversity analyses revealed significant differences only between stable and persistent GAgP groups ( p = .004). Conclusion: Patients with persistent AgP showed a more dysbiotic subgingival biofilm than those who have been successfully treated. It remains to be established whether such differences were predisposing to disease activity or were a result of a dysbiotic change associated with disease recurrence in the presence of sub‐standard supportive periodontal therapy or other patient‐related factors.